Analisis ANALISIS KUALITAS PRODUK DAN KUALITAS PELAYANAN HOLLAND BAKERY SE-SOLO RAYA SERTA PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN: Kualitas Produk, Kualitas Pelayanan, dan Keputusan Pembelian Pelanggan - syahnaf putri revilia sholaimah (STIE Wijaya Mulya, 2025)
This study examines the influence between the quality of a product and its service on customer purchasing decisions in Solo Raya through quantitative research with a descriptive approach, data collection strategies include distributing questionnaries made using a goggle form to 96 respondents who have made at least one transaction at Holland Bakery. This techniques used are the classical assumption test, normality test, multiple linier regression analysis test, and hypothesis testing. Which shows that there is significant and positive influence on product quality and service quality on customer purchasing decisions. Based on the findings of this research, improving product quality and service quality helps Holland Bakery retain and attract new consumer to Holland Bakery. It is hoped that this research will be able to contribute to companies in developing more efficient and optimal marketing strategies.